Dimensi Etis Iklan, Studi Kasus Pada Iklan Sampo Anti Dandruff dan Iklan Belanja Online di Media Televisi - Ni Luh Putu Ratna Suandari; Fajri Rahma Pratiwi; Handriyotopo Handriyotopo (ISI Press Institut Seni Indonesia Surakarta, 2021)
The ethical dimension related to advertising ethics towards advertisements broadcast on television media often violates the rules. The case study of the Pantene advertisement version of